2019
DOI: 10.1002/adfm.201901419
|View full text |Cite
|
Sign up to set email alerts
|

Tension Pistons: Amplifying Piston Force Using Fluid‐Induced Tension in Flexible Materials

Abstract: Pistons are ubiquitous devices used for fluid-mechanical energy conversion. However, despite this ubiquity and centuries of development, the forces and motions produced by conventional rigid pistons are limited by their design. The use of flexible materials and structures opens a door to the design of a piston with unconventional features. In this study, an architecture for pistons that utilizes a combination of flexible membrane materials and compressible rigid structures is proposed. In contrast to conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…These reasons have been pushing the scientific community to explore new ways to implement pneumatic actuators. Several approaches have been followed, namely, by (i) using flexible materials [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ] to embody the actuator, (ii) using hybrid electric-pneumatic actuators that combine the simpleness of control of electrical actuators with the pneumatic actuators low stiffness [ 11 , 12 ], and (iii) developing a new piston configuration to increase the energetic efficiency of conventional cylinders [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reasons have been pushing the scientific community to explore new ways to implement pneumatic actuators. Several approaches have been followed, namely, by (i) using flexible materials [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ] to embody the actuator, (ii) using hybrid electric-pneumatic actuators that combine the simpleness of control of electrical actuators with the pneumatic actuators low stiffness [ 11 , 12 ], and (iii) developing a new piston configuration to increase the energetic efficiency of conventional cylinders [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A novel idea that has recently been presented in [8] is the use of a deformable piston structure covered by a flexible membrane: the so-called tension piston. Significant energy improvements are claimed in [8], as the configuration allows pneumatic energy to be converted into mechanical energy using two different ways: pressure on the piston rigid areas and a pneumatic-induced tension on the piston flexible membrane. This configuration presents some potential advantages over conventional techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Since a flexible membrane is used for sealing, it has no leakages and exhibits low friction forces, making it potentially more appealing for servo control. In addition, in [8], it is shown that the tension piston can develop higher forces when compared to a conventional piston at the same pressure. Although the authors of [8] sustain that this leads to substantially higher power and energy efficiency, the conventional actuator used for comparison in [8] uses conventional seals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations